PENGARUH JENIS ELEKTRODA PENGELASAN SMAW TERHADAP KEKUATAN LAS BAJA KARBON RENDAH - Nurmala Shanti Dera; Idris Sahidu; Sahionl Ishak; Novriyanti Talango; Wawan Rauf (Journal of Vocational Education and Automotive Technology, 2025)
Low carbon steel such as ST 37 is widely used in manufacturing and construction industries due to its ease of fabrication and cost-effectiveness. However, one of its main drawbacks is its relatively low hardness and wear resistance, especially after welding processes. The Shielded Metal Arc Welding (SMAW) method is highly influenced by the type of electrode used, which significantly affects the mechanical properties of the weld joint. This study aims to investigate the effect of electrode variation (E6010, E6013, and E7018) on the mechanical properties of ST 37 low carbon steel after undergoing thermochemical treatment using the pack carburizing method. An experimental quantitative approach was used in this research. ST 37 steel samples were welded using three different types of electrodes, followed by pack carburizing at 950°C for two hours using coconut shell charcoal as the carbon source, and then quenched in oil. Mechanical properties were evaluated through tensile and hardness tests, including calculations of strain and elastic modulus. The results showed that the E6010 electrode provided the best performance, with the highest average tensile strength of 25.835 MPa and the highest strain value of 0.2667, indicating strong and ductile weld joints. In contrast, the E7018 electrode yielded the highest elastic modulus at 104.363 MPa, reflecting a stiffer but less ductile material. These findings confirm that electrode selection plays a critical role in determining the mechanical behavior of welds, particularly when combined with surface hardening treatments like pack carburizing. This study contributes to scientific understanding and offers practical recommendations for improving weld quality in both industrial and academic contexts.